2019
DOI: 10.3390/cancers11060759
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Epstein-Barr Virus Infection in Non-Small Cell Lung Cancer

Abstract: Previous investigations proposed a link between the Epstein-Barr virus (EBV) and lung cancer (LC), but the results are highly controversial largely due to the insufficient sample size and the inherent limitation of the traditional viral screening methods such as PCR. Unlike PCR, current next-generation sequencing (NGS) utilizes an unbiased method for the global assessment of all exogenous agents within a cancer sample with high sensitivity and specificity. In our current study, we aim to resolve this long-stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 84 publications
(110 reference statements)
3
48
0
Order By: Relevance
“…It was also shown that EBV infection is associated with a reduction of the number of CD4 + Tlymphocytes in patients with EBV-related cancer (20). Despite the involvement of EBV infection in the development of cancer having been extensively studied (5,8,9,(21)(22)(23)(24)(25)(26)(27), reports analyzing the initial phase of immune response and lymphocyte activation affected by viral infection are rare. During primary EBV infection, antibodies to VCA IgM are generated and persist from weeks to months.…”
Section: Discussionmentioning
confidence: 99%
“…It was also shown that EBV infection is associated with a reduction of the number of CD4 + Tlymphocytes in patients with EBV-related cancer (20). Despite the involvement of EBV infection in the development of cancer having been extensively studied (5,8,9,(21)(22)(23)(24)(25)(26)(27), reports analyzing the initial phase of immune response and lymphocyte activation affected by viral infection are rare. During primary EBV infection, antibodies to VCA IgM are generated and persist from weeks to months.…”
Section: Discussionmentioning
confidence: 99%
“…158,159 The association of EBV and lung cancer presents significant differences according to tumor histotype and geographical site. 15,160 The EBV is often detected in pulmonary LELC occurring in patients from east and southeast Asia where nasopharyngeal carcinoma is highly prevalent, 13,[161][162][163][164] but rarely detected or even undetected in other types of lung cancer such as adenocarcinoma, squamous cell carcinoma, and SCLC. 42,165,166 Recently, Wang et al explored the EBV genomic variations in lung carcinoma and reported four newly sequenced EBV genomes isolated from primary lung carcinomas with apparent genomic diversity among these EBV genomes.…”
Section: Epstein-barr Virus (Ebv)mentioning
confidence: 99%
“…It is believed, that both genetic, as in family history and polymorphisms, and environmental risk factors are responsible for lung cancer; smoking being the major risk factor for this disease [3,4]. Several recent studies have highlighted infectious agents such as bacteria [5][6][7] and viruses [8][9][10][11] as high-risk factors of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…It is projected that at least 20% of all human cancers are attributed to microorganisms' infections including viral [12]; viruses are linked with the onset of both solid and hematological malignancies in humans [13]. Some of the frequently linked oncoviruses with lung cancer include Epstein Barr virus (EBV), hepatitis viruses B and C (HBV and HCV), and human papillomaviruses (HPVs) [8,9,11]. However, their causal relationship to lung cancer has not been established yet.…”
Section: Introductionmentioning
confidence: 99%